Stakeholder engagement for inclusive water governance in a rural community in Brazil - Moreira, Fernanda Deister; Fonseca, Paula Rafaela Silva; Miranda, Raquel Machado; Oliveira da Costa, Luana; Mejias Carpio, Isis Elaine (Frontiers in Water, 2024)
Stakeholder engagement is an integral part of water governance to provide long-term sustainable water services (e.g. water storage, distribution, treatment ). Yet, evidence-based studies documenting how community engagement contributes to water governance objectives are scarce. This Community Case Study describes key findings of a three-year experience by Global WaSH executing the Água Viva Program. The study recounts the process of building community engagement among stakeholders in the rural district of Monte Verde de Minas, in the city of Juiz de Fora, Brazil. The study is presented through the viewpoint of the Bridging Organization, Global WaSH. The Program had four main phases: Discovery and Planning, Awareness, Engagement, and Intervention. This study demonstrates the importance of multi-stakeholder participation and the crucial role of the community to reach sound governance. This article also shares the challenges of connecting the interests of distinct actors. It emphasizes the role of a team of WaSH specialists with relationship-building experience in merging community demands and government concerns.